ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AUDITOR SWITCHING PADA PERUSAHAAN BUMN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ayu Nir’atunnisa Setyaningrum; Bambang Agus Pramuka; Siti Maghfiroh; Dona Primasari (Jurnal Riset Akuntansi Soedirman (JRAS), 2022)
This study aims to determine the effect of several factors, namely the size of KAP, management change, and financial distress on auditor switching in BUMN companies listed on the IDX for the period 2015-2019. Auditor switching is an important issue because it relates to the change of KAP or auditors in companies that can affect the audit results of their financial statements. This study focuses on voluntary auditor switching or outside of the applicable regulations. The population in this study were all state-owned companies listed on the IDX in 2015-2019. The sample was selected using a purposive sampling technique with the number of samples obtained as many as 75 samples. Data collection was carried out using the documentation method based on available information and data. The data analysis method used is logistic regression analysis and the processing is assisted by the IBM SPSS version 26 application. The results of this study indicate that: (1) KAP size has a significant negative effect on auditor switching; (2) management change has no effect on auditor switching; and (3) financial distress has no effect on auditor switching. The implication of the results of the research above is that companies need to change KAP or auditors in accordance with applicable regulations even though they have used large KAPs. Each company is also expected to be able to choose an auditor based on expertise in their field, not just based on the size of the KAP. Auditors from every KAP who are given excessive trust by clients and investors are expected to maintain their professionalism and independence by working objectively and not violating the code of ethics.